Oil Spill Biodegradation by Bacteria Isolated from Jakarta Bay Marine Sediments - Angga Dwinovantyo; Tri Prartono; Restya Rahmaniar; Nico Wantona Prabowo; Santi Susanti (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2016)
A laboratory study was conducted with the aim to isolate and identify bacteria from sea sediment and test their biodegradation ability in two place where contaminated with oil spill. Five sediment samples were dissolved by using sterile sea water, and then bacteria isolated with total plate count (TPC) method. Isolates bacteria was cultivated, and adapted using the nutrient conditioned sea water medium. Biodegradation process was done by mixing the bacteria with crude oil and shaken for few days. The number of bacteria isolated varied from 2 x 102 CFU ml-1 to 6 x 106 CFU ml-1 and apparently increased after cultivation and adaptation with oily media. Bacteria identified during this study were Fundibacter sp., Alcanivorax sp., and Marinobacter sp.. The result of biodegradation process was statistically analyzed and obtained that the bacteria are effective in degrading oil in seven days with constant of biodegradation rate was 0.1766. GC-MS analysis was conducted to prove the decomposition of carbon chain by bacteria and revealed oil degradation in carbon number 11 to 27. Based on all analysis, marine sediment bacteria can degrade the oil spill. Keywords : Bacteria, Biodegradation, GC-MS, Marine Sediments, Oil spill.